2002
DOI: 10.1039/b110038f
|View full text |Cite
|
Sign up to set email alerts
|

Fluorimetric analysis of lipase hydrolysis of intermediate- and long-chain glycerides

Abstract: For the purpose of deducing the digestive behavior of dietary fat in the digestive organs, a fluorimetric method for the measurement of hydrolysis by porcine pancreatic lipase was performed using intermediate- and long- acyl chain glycerides as substrates. Insoluble glycerides constituted by C10-C16 acyl chains were mechanically dispersed in 100% buffer and hydrolyzed by porcine pancreatic lipase. After the reaction, fatty acid released by the enzyme was extracted and its carboxyl group was fluorescently label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Despite the diverse studies that have reported the controversial about digestion, absorption, and transport of ω‐3 concentrates under different forms, the study of the lipid content and composition of the MP formed during luminal metabolism of these lipids is scarce. Several studies have been carried out regarding composition of the whole digestion medium by in vitro assays 3, 7–9 but most of them did not deal with the potentially absorbable fraction, which might be the hydrolysis products included in the MP.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the diverse studies that have reported the controversial about digestion, absorption, and transport of ω‐3 concentrates under different forms, the study of the lipid content and composition of the MP formed during luminal metabolism of these lipids is scarce. Several studies have been carried out regarding composition of the whole digestion medium by in vitro assays 3, 7–9 but most of them did not deal with the potentially absorbable fraction, which might be the hydrolysis products included in the MP.…”
Section: Introductionmentioning
confidence: 99%
“…A series of N-(tert-butoxycarbonyl)-neurotransmitter amino acids 1 (glycine, alanine, glutamic acid, β-alanine and γ-aminobutyric acid) were reacted with 9-bromomethylacridine 2 25 to afford the corresponding heterocyclic ester derivatives 3, via a potassium fluoride coupling in N,Ndimethylformamide, at room temperature (Scheme 1 and Table 1). 27 The acridin-9-yl methylene group will be designated in this report by a three-letter code (Acm) for simplicity of naming the various fluorescent derivatives, as indicated in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Chloroform ( In view of the current use of 9-bromomethylacridine as HPLC derivatizing agent for fluorescent labelling of carboxylic acids, 25,26 the present work represents a novel application, indicative of its versatility and as a result this azaheterocycle can be regarded as an addition to the collection of photolabile protecting groups for the carboxylic acid function.…”
Section: Additionally To Monitoring the Photolysis Process By Hplc/uvmentioning
confidence: 99%
See 1 more Smart Citation
“…5, compared to the normal hydrolysis process of TB. Other reasons related to the own etherified alkyl chain, the hydrophobicity of the whole molecule or the steric structure, might influence the interaction of the enzyme with alkylglycerols and explain the different course of reaction respect to TB [30,31].…”
Section: Discussionmentioning
confidence: 98%